2022
DOI: 10.3390/metabo12040336
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thyroid Hormones on Skeletal Muscle Thermogenesis

Abstract: Nowadays obesity becomes a significant global problem. Hence, recently more and more attention has been paid to substances present in the body that have a significant impact on metabolic processes and thermogenesis, in the context of their potential use in the prevention and treatment of obesity. It is well known that the relationship between thyroid hormones and obesity is multilayered, however recently, more and more information about the possible relation between thyroid hormones and muscle metabolism has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
8
0
1
Order By: Relevance
“…In an in vitro study by Vaughan et al [ 76 ], it was found that trypsin-treated myocytes demonstrated enhanced oxidative metabolism and mitochondrial biogenesis and increased expression of UCP3. Therefore, irisin and UCP3 may play an important role in shivering thermogenesis [ 77 ]. Thus, when exposed to low temperatures, shivering thermogenesis is activated in the body, which is accompanied by a contraction of skeletal muscles, during which irisin is released and UCP3 expression begins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an in vitro study by Vaughan et al [ 76 ], it was found that trypsin-treated myocytes demonstrated enhanced oxidative metabolism and mitochondrial biogenesis and increased expression of UCP3. Therefore, irisin and UCP3 may play an important role in shivering thermogenesis [ 77 ]. Thus, when exposed to low temperatures, shivering thermogenesis is activated in the body, which is accompanied by a contraction of skeletal muscles, during which irisin is released and UCP3 expression begins.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data have shown that ROS production is increased in mice with knockout UCP3 [ 79 , 80 ]. Since irisin can stimulate mitochondrial biogenesis [ 77 ], in which the number of mitochondrial copies in myocytes increases to produce a large volume of ATP, the amount of ROS increases and lipid peroxidation processes are activated. The uncoupling protein UCP3 inhibits the production of ROS in mitochondria, by reducing the mitochondrial membrane potential [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the HPT axis has a direct impact on energy homeostasis and an imbalance within the axis can make an organism more vulnerable to developing metabolic disorders and obesity [ 168 ]. Among the major physiological processes affected by thyroid hormones are energy expenditure, thermogenesis, liver metabolism, bone homeostasis, and cardiovascular function [ 169 , 170 , 171 , 172 , 173 , 174 ]. Selenium plays an essential role in the HPT axis as the DIO selenoprotein sub-family is responsible for the activation and de-activation of thyroid hormones via deiodination [ 175 , 176 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%
“…Відмічено також зсув ІМТ від більш високих значень до показників, близьких до нормального рівня, що як вважаємо, вдалося досягти завдяки поєднанню метформіну із левотироксином. Беручи до уваги дані, отримані іншими дослідниками, можемо стверджувати, що не лише прямий влив метформіну на ІР та левотироксину на відновлення метаболізму міг мати ефект відносно ваги пацієнтів, а також дія даних препаратів на ХІТ та здатність впливати на композицію КМ [5,7,8].…”
Section: результати та їх обговоренняunclassified